SISTEM INFORMASI KUIS ELEKTRONIK (E-QUIZ) PRAKTIKUM LABORATORIUM KOMPUTER D3 KOMPUTER DAN SISTEM INFORMASI UNIVERSITAS GADJAH MADA - , TAUFIQ RAMADHAN; , Yunita Sari, S.Kom., M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Computer laboratories is one of the facilities in the department of D3 Komputer dan Sistem Informasi Universitas Gadjah Mada to support student conducting practicum subjects. Just like the cognitive learning in the classroom, in the practicums there are quizzes that used as a method for evaluate the learning process that have been held. Currently, the quiz is done without any computerized system. Quizâs questions is written on the board or displayed by the projector. The students write their answers on the paper then submit it to the assistant to be checked. The process is inefficient as the students need to rewrite the questions that have been given before. In addition, the marking process will be tedious when the studentsâs answer is illegible, or answer sheets torn, dirty, or even lost . When the quiz is completed, the students often do not know the score so it can not used an evaluation for them. Based on these issues, we need a system that could be able to handle the lab quiz. Thus, it can reduce the inefficiencies and the errors in the quiz process. Electronic Quiz Information Systems of Practicum Computer Laboratory of Computer and Information System Vocational School Universitas Gadjah Mada is developed to solve the problems. Hopefully with this system, the quiz process will be more efficient and will reduce the errors in the marking process. Electronic Quiz Information Systems of Practicum Computer Laboratory of Computer and Information System Vocational School Universitas Gadjah Mada have been developed using Laravel framework and MySQL DBMS. The system has certain features such as laboratory data management, quiz process, automatic marking for multiple choice quiz, quiz archive, question bank, and score management.